Activity of Superoxide Dismutase and its Relationship with Some Trace Elements in Plasma of Sickle Cell Anemia Patients - هاشم عبدالكريم; كريم رافد; علي داود (Iraqi Journal of Science, 2025)
The study was dealing with isolation , purification and evaluation activity of SuperOxide Dismutase ( SOD ) in patients with sickle cell anemia type HbS/F and HbS/S. The result was revealed a significant decreases in values of total SOD activity in plasma of patients with both type sickle cell anemia as compared with healthy individuals (control) , furthermore the total enzyme activity was more decreased in type HbS/S than type HbS/F, total SOD activity was determined by riboflavin / nitrobluetetrazolium assay.The result was also revealed a significant decrease in zinc level while the level of copper was increased in both patient plasma in comparisonThe purification procedure represented by using some solvents and precipitation by acetone then gel filtration on Sephadex – G100 column .The overall purification folds and the yield of the enzyme purified from control group were 7.33 and 72.34 % respectively while the from patients group were 7.03 and 64.81 % respectively .